Differentiation of Alzheimer's disease from other neurodegenerative disorders using chemiluminescence immunoassays measuring cerebrospinal fluid biomarkers - Arendt, Philipp; Römpler, Katharina; Brix, Britta; Borchardt-Lohölter, Viola; Busse, Mandy; Busse, Stefan (Frontiers in Dementia, 2024)
Introduction: Prior research identified four neurochemical cerebrospinal fluid (CSF) biomarkers, Aβ1 42, Aβ1 40, tTau, and pTau(181), as core diagnostic markers for Alzheimer’s disease (AD). Determination of AD biomarkers using immunoassays can support differential diagnosis of AD versus several neuropsychiatric disorders, which is important because the respective treatment regimens differ. Results of biomarker determination can be classified according to the Amyloid/Tau/Neurodegeneration (ATN) system into profiles. Less is known about the clinical performance of chemiluminescence immunoassays (ChLIA) measuring specific biomarkers in CSF samples from patients suffering from neuropsychiatric impairments with various underlying causes. Methods: ChLIA (EUROIMMUN) were used to determine Beta-Amyloid (1-40), Beta-Amyloid (1-42), Total-Tau, and pTau(181) concentrations in precharacterized cerebrospinal fluid (CSF) samples from 219 AD patients, 74 patients with mild cognitive impairment (MCI), and 220 disease control (DC) patients. Results: 83.0% of AD patients had ATN profiles consistent with AD, whereas 85.5% of DC patients and 77.0% of MCI patients had profiles inconsistent with AD. AD patients showed significantly lower amyloid ratio Aβ1-42/Aβ1-40 (mean: 0.07) and significantly higher concentrations of tTau (mean: 901.6 pg/ml) and pTau(181) (mean: 129 pg/ml) compared to DC and MCI patients (all p values < 0.0071). Discussion: The ChLIAs effectively determined specific biomarkers and can support differential diagnostics of AD. Their quality was demonstrated in samples from 513 patients with cognitive impairments, representing a realistic mix of underlying causes for seeking treatment at a memory clinic.